2012
DOI: 10.4172/2155-6202.10000120
|View full text |Cite
|
Sign up to set email alerts
|

Biopesticidal Formulation Of Beauveria Bassiana Effective Against Larvae Of Helicoverpa Armigera.

Abstract: The present study was to emphasize entomopathogens in pest management of cash crops over chemical pesticides, optimization of media for growth of Beauveria bassiana and bioassay of different formulations for their efficacy as marketable and easily applicable biopesticide. Beauveria bassiana (Order: Hypocreales, Family: Cordycipitaceae) popularly known as white muscardine entomogenous fungi was isolated from soyabean fields of Misrod, Bhopal. Media for optimal growth of fungus were standardized. Its different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Inconsistent efficacy of EPF‐based biopesticides under different environmental conditions could therefore be addressed through improved formulations. For example, Ritu et al () demonstrated that incorporating bentonite in oil‐based formulation of B. bassiana improved its efficacy against Helicoverpa armigera (Hübner; Lepidoptera: Noctuidae).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent efficacy of EPF‐based biopesticides under different environmental conditions could therefore be addressed through improved formulations. For example, Ritu et al () demonstrated that incorporating bentonite in oil‐based formulation of B. bassiana improved its efficacy against Helicoverpa armigera (Hübner; Lepidoptera: Noctuidae).…”
Section: Discussionmentioning
confidence: 99%
“…Although organic compounds are commonly used, inorganic materials also take part in formulations. Geomaterials such as zeolites, talc, bentonite and kaolin have been used as main components or as additives in fungal formulations (Daoust et al, 1983;Kucuk and Kivanc, 2005;Ezzati-Tabrizi et al, 2009;Ritu et al, 2012), providing stability and low cost and easy accessibility, mainly in countries where vast amounts of such materials are available and underexploited.…”
Section: Introductionmentioning
confidence: 99%
“…Ricano et al [20] found that using more than one formula of B. bassiana can remarkably reduce survival and increase mortality rate among red palm weevil larvae and adults. B. bassiana can increase mortality rate of Helicoverpa armigera larvae as well as mentioned by Ritu et al [21]. Such practice, using entomopathogenic fungi infested of conventional insecticides which failed in achieving acceptable control level, could be effective alternative and sound method from ecological and health view points.…”
Section: Efficacy Of Entomopathogenic Fungi On Oryctes Spp Larvaementioning
confidence: 92%